2013
DOI: 10.1515/ijnes-2012-0027
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Contingencies on Nursing Students’ Reactions During a Rural Clinical Placement

Abstract: Students' feedback of their practicum experiences are typically documented only in terms of established nursing competencies and learning objectives. How nursing students cope with social contingencies (e.g., personal health) while away on clinical placement is not commonly reported in the literature. A sample of Australian student nurses was surveyed as a way of contributing new knowledge about what and how social contingencies could impact on a practicum experience. An analysis of the survey data provided by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…This means that students with lower study level are more likely to accept assignment to a rural area. A study by Kerr in Australia also revealed that first year students experienced less stress and had less commitment to professional organisations than their seniors during a rural clinical placement 32. The study showed that the younger students were more flexible in choosing their working placement.…”
Section: Discussionmentioning
confidence: 94%
“…This means that students with lower study level are more likely to accept assignment to a rural area. A study by Kerr in Australia also revealed that first year students experienced less stress and had less commitment to professional organisations than their seniors during a rural clinical placement 32. The study showed that the younger students were more flexible in choosing their working placement.…”
Section: Discussionmentioning
confidence: 94%
“…As shown in the data chart (online supplemental appendix B) and summary of included literature (table 2), most of the literature is based in the Australian context (n=77) 8 22 27–101. There is variability in the sites in which student placements were undertaken, and the length of placement varied from 6 days to 52 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…However, the evidence on the effect of rural placement on rural practice intention for nursing and allied health students is less clear (Playford, Larson, & Wheatland, 2006). Generally, there is a lack of literature specific to nursing and allied health student placements (Bazen, Kruger, Dyson, & Tennant, 2007;Johnson & Blinkhorn, 2011;Orpin & Gabriel, 2005;Sutton et al, 2016) and, more specifically, on the social contingencies of rural student placements (Kerr, Hemmings Brian, & Kay, 2013;Lea et al, 2008). Furthermore, there is a paucity of literature written from the perspective of the students themselves (Dalton et al, 2002;White & Humphreys, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Second, nursing and allied health students frequently describe rural health services as being positive, friendly work environments (Johnson & Blinkhorn, 2011;Lea et al, 2008;Schofield et al, 2009;Sutton et al, 2016) where they receive dedicated support from staff and clinical supervisors (Australia, 2015;Johnson & Blinkhorn, 2011;White & Humphreys, 2014). Third, students report more opportunities for hands-on learning experiences, exposure to a broader scope of practice (Lea et al, 2008;Orpin & Gabriel, 2005;Paterson, McColl, & Paterson, 2004;Webster et al, 2010) and being provided the opportunity to be more responsible and autonomous in their practice (Adams et al, 2005;Kerr et al, 2013;Killam, Carter, & Carter, 2010;Schofield et al, 2009;Sutton et al, 2016) in their rural placements. Most of these rural-specific factors are well identified in the literature, but others are less common, including: enjoying increased opportunities to work in an inter-professional health team (Adams et al, 2005;Devine, 2006), enjoyment of immersion into new settings (Bazen et al, 2007;Daly, Perkins, Kumar, Roberts, & Moore, 2013;Thackrah, Thompson, & Durey, 2014), having more time to develop satisfying patient relationships (Daly et al, 2013;Orpin & Gabriel, 2005) and increased career opportunities following rural placement (Adams et al, 2005;Paterson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation